Clinical features and prognosis of paraquat poisoning in French Guiana: A review of 62 cases. Issue 15 (April 2018) - Elenga, Narcisse; Merlin, Caroline; Le Guern, Rémi; Kom-Tchameni, Rémi; Ducrot, Yves-Marie; Pradier, Maxime; Ntab, Balthazar; Dinh-Van, Kim-Anh; Sobesky, Milko; Mathieu, Daniel; Dueymes, Jean-Marc; Egmann, Gérald; et al.
Abstract : Abstract: Paraquat is a nonselective contact herbicide of great toxicological importance, being associated with high mortality rates. Because of its high toxicity, the European Union withdrew it from its market in 2007. The aim of this study is to analyze all cases of paraquat poisoning hospitalized in French Guiana in order to assess their incidence and main characteristics. Medical records of all paraquat intoxicated patients hospitalized from 2008 until 2015 were reviewed in this retrospective study. Demographics, clinical presentation, and laboratory data were evaluated. A total of 62 cases were reviewed. The incidence of paraquat poisoning was 3.8/100, 000 inhabitants/year. There were 44 adults and 18 children younger than 16 years of age. The median ages were 31 years [18.08–75.25] in adults and 13.4 years [0.75–15.08] in children, respectively. The median duration of hospitalization was longer in children [15.5 days (1–24)] than in adults [2 days (1–30)], P < .01. The majority of cases was due to self-poisoning (84%). Children had ingested a lower quantity of paraquat [48.8 mg/kg (10–571.1)] than adults [595.8 mg/kg (6–3636.4), P = .03]. There were more deaths among adults (65%) than in children (22%), P = .004. The severity and outcome was determined primarily by the amount of paraquat ingested. In conclusion, French Guiana has the largest cohort of paraquat poisonings in the European Union. The major factor affecting the prognosis of patients was the ingested amount of paraquat. The administration of activated charcoal or Pemba, in situ, within the first hour after ingestion of paraquat is essential.